Evaluation of Sn(ii) aminoalkoxide precursors for atomic layer deposition of SnO thin films. Issue 39 (16th September 2021) - Parish, James D.; Snook, Michael W.; Johnson, Andrew L.
Abstract : A series of homo- and hetero-leptic Sn(ii ) aminoalkoxide complexes have been synthesised, characterised and the thermal properties of the homoleptic complexes assesed for their potential as ALD precursors for SnO thin films. Abstract : We have successfully prepared and structurally characterized a family of eight tin(ii ) heteroleptic complexes, [Sn(NR2 )(ON)] x (NR2 = NMe2 (1a–d ) or N(SiMe3 )2 (2a–d ); x = 1 or 2) and four homoleptic systems, [Sn(κ 2 -ON)2 ] (3a–d ) from a series of aminoalcohols and fluorinated aminoalcohols (HON) having a different number of methyl/trifluoromethyl substituents at the α-carbon atom, [HOC(R 1 )(R2 )CH2 NMe2 ] (R 1 = R 2 = H (Hdmae) (a); R 1 = H, R 2 = Me (Hdmap) (b); R 1 = R 2 = Me (Hdmamp) (c); R 1 = R 2 = CF3 (HFdmamp) (d)). The synthetic route used reactions of either [SnN(SiMe3 )2 2 ] or [Sn(NMe2 )2 ] with one or two equivalents of the aminoalcohols (a–d) in dry aprotic solvents leading to elimination of amines and formation of the Sn(ii ) species 1a–d, 2a–d and 3a–d respectively. All complexes were thoroughly characterized by NMR spectroscopy ( 1 H, 13 C, 19 F, and 119 Sn) as well as single-crystal X-ray diffraction studies. In all case the solid state molecular structures of the complexes have been unambiguously established: the solid state structures 1a–b and 1c are dimeric with central Sn2 N2 cores resulting from bridging μ 2 -NMe2 units, in which the Sn(ii ) atoms are four-coordinate. In contrast, the solid state structures of complexes 1c and 2a–c possess similarly dimeric structures, with four-coordinate Sn(ii ) atoms, in which the oxygen atoms of the ON ligand bridge two Sn(ii ) centres to form dimers with a central Sn2 O2 core. Uniquely in this study, 2d, [Sn(κ 2 -O, N-OCMe2 CH2 NMe2 )N(SiMe3 )2 ] is monomeric with a three coordinate Sn(ii ) centre. The homoleptic complexes 3a–d are all isostructural with monomeric four-coordinate structures with disphenoidal geometries. Solution state NMR studies reveal complicated ligand exchange processes in the case of the heteroleptic complexes 1a–d and 2a–d . Contrastingly, the homoleptic systems 3a–d show no such behaviour. While complexes 1a–d and 2a–d displayed either poor thermal stability or multistep thermal decomposition processes, the thermal behaviour of the homoleptic complexes, 3a–d, was investigated in order to determine the effects, if any, of the degree of fluorination and asymmetry of the aminoalkoxide ligands on the suitability of these complexes as ALD precursors for the deposition of SnO thin films.